Too Little, Too Late: Consent Education, Sexual Practice, and Institutional Power in College Life - Dayton, Allison; Standlee, Alecea (Qualitative Sociology Review, 2026)
Despite widespread efforts to address sexual assault on US college campuses through consent education, understanding and practicing consent remains a complex and under-researched area. Consent, defined as clear, continuous, and voluntary communication, is often emphasized as a preventive measure against sexual assault. However, high rates of sexual assault, particularly among college students, highlight the limitations of current educational approaches. Our study examines college students’ conceptualizations of consent, their application of consent in sexual relationships, and their views on the effectiveness of consent education. Findings indicate that many students harbor concerns about consent education, particularly regarding best practices, the influence of alcohol, and individual interpretations of consent. Notably, students report that their educational experiences have a limited impact on their understanding of and practices regarding consent, and they often struggle to apply these concepts effectively in real-world contexts. These findings underscore the need for more nuanced and impactful educational consent strategies that address the complexities of consent in intimate relationships and provide clearer guidance on managing factors like alcohol. This research aims to inform more effective approaches for activists and educational institutions in reducing campus sexual assault.